The Effect of Intravenous Peramivir, Compared with Oral Oseltamivir, on the Outcome of Post-Influenza Pneumococcal Pneumonia in Mice. Issue 1 (January 2015) - Tanaka, Akitaka; Nakamura, Shigeki; Seki, Masafumi; Iwanaga, Naoki; Kajihara, Toshiki; Kitano, Mitsutaka; Homma, Tomoyuki; Kurihara, Shintaro; Imamura, Yoshifumi; Miyazaki, Taiga; Izumikawa, Koichi; Kakeya, Hiroshi; et al.
Background: Pneumococcal pneumonia often occurs secondary to influenza infection and accounts for a large proportion of the morbidity and mortality associated with seasonal and pandemic influenza outbreaks. Peramivir is a novel, intravenous neuraminidase inhibitor that exhibits potent antiviral activity against influenza A and B viruses. We investigated the efficacy of peramivir for modulating the severity of secondary pneumococcal pneumonia. Methods: CBA/JNCrlj mice, infected with influenza virus and superinfected with Streptococcus pneumoniae, were treated with either intravenous peramivir (single or multiple doses of 60 mg/kg/day) or oral oseltamivir at doses of 10 or 40 mg/kg/day in divided doses. The survival rate, viable bacterial count and virus titre in the lungs, as well as cytokine/chemokine concentration and histopathological findings were compared between both groups. Results: The median duration of survival of coinfected mice was significantly prolonged by treatment with multiple doses of peramivir, relative to mice treated with oseltamivir at either dose. Viable bacterial counts and virus titres in the lungs were significantly reduced by intravenous peramivir treatment compared with no treatment or oral oseltamivir treatment. The production of inflammatory cytokines/chemokines was also significantly suppressed by multiple dosing of peramivir compared with oseltamivir. Increased survival appeared to be mediated by decreased inflammation, manifested as lower levels of inflammatory cells and proinflammatory cytokines in the lungs and less severe histopathological findings. The lungs of mice treated with multiple doses of peramivir showed mild inflammatory changes compared to oseltamivir. Conclusions: This study demonstrated that a multiple-dose regimen of intravenous peramivir was more efficacious than a single peramivir dose or multiple doses of oseltamivir for improving outcomes in pneumococcal pneumonia following influenza virus infection in mice.